(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
• This research aims to investigate the nature of the correlated relationship between mindfulness and resilience, as well as to investigate these differences according to the gender variable. The Kentucky Inventory of Mindfulness (prepared by Baer, Gregory, and Allen, 2004) and Resilience Scale (prepared by Connor and Davidson, 2003), both translated into Arabic by Al-Assemi, have been used. The sample consisted of (40) 3th year undergraduate students of Counseling Department (2nd Faculty of Education in Damascus University). The concluded results are: • There is a statistically significant relationship between observing and resilience dimensions: hardiness, resourcefulness, and purpose, as well as the total score of resilience. Moreover, there is a statistically significant relationship between describing and purpose dimensions. Furthermore, there is a statistically significant relationship between the total score of resilience and the purpose dimension. • There are statistically significant differences in the average scores among the sample’s members on the resilience scale between high and low emotional regulation levels.‎ • There are no statistically significant differences in the average scores among the sample’s members on the mindfulness and resilience scales related to gender.‎ • There is a statistically significant effect between resilience and gender variables in mindfulness, in favor of high-scored resilience female members. However, there is a statistically significant effect of resilience alone or gender alone in mindfulness.